Contested, Impractical, and Easily Forgotten? Analysing National-Level Decision-Makers’ Interpretations of Lessons Learned From the COVID-19 Pandemic Through a Qualitative Follow-up Study - Janhonen, Kristiina; Viita-aho, Marjaana; Paananen, Henna; Kihlström, Laura; Karreinen, Soila; Tynkkynen, Liina-Kaisa (Scandinavian Journal of Public Administration, 2025)
This article employs Dewey’s pragmatist theory and a follow-up study design to explore how Finnish national-level decision-makers perceived and interpreted lessons learned at two different time points during the crisis: first during the acute stage in 2021 (n = 21) and later following the stage of high vaccination coverage and the conclusion of the acute stage in 2022–2023 (n = 16; 15 of which took part also in the first interview and 1 having transferred to a key role after 2021). Interviewees represent key ministries, other national governmental organizations with pandemic governance responsibilities, expert organizations, and authorities responsible for preparedness. Analyses aimed to construct a more comprehensive understanding of the COVID-19 pandemic, and explore lessons learned as situationally emerging, evolving, and processual. Results reveal how lessons were intertwined with political decision-making, experienced as temporally impractical and easily forgotten, and shaped through a dichotomy of crisis and normalcy. For further research on crisis lessons, we call for greater acknowledgement of the politicized nature of defining lessons learned, measures to overcome the tendency of lessons to fade, and management of continuity across the crisis-normalcy divide. Conclusions offer suggestions for overcoming these difficulties in preparation for future crises.